1994
DOI: 10.1007/bf00408476
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of preclinical IDDM in high risk siblings

Abstract: To learn more about the preclinical phase of IDDM we observed for a median period of 46.5 months (range 0.5-69 months) a group of 57 siblings positive for ICA and/or IAA when first screened within 6 months of the diagnosis of the proband. Sequential blood samples and IVGTTs were obtained at intervals of 6-12 months. Seventeen siblings (29.8%) presented with IDDM during the observation period. The duration of the known preclinical period ranged from 0.5 to 51 months (median 29 months). The converters were young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…It is also noteworthy that despite lower insulin levels during the IVGTT, the relatives of diabetic patients -especially these with positive autoantibodies -had significantly higher fasting insulin concentrations and higher HOMA-IR index than had the controls. Moreover, a positive correlation between IAA levels and HOMA-IR was found in the study group, confirming the previous observations suggesting that not only decreased beta-cell secretory reserve, but also increased insulin resistance, impact upon the progression of the autoimmune process, especially in subjects with auto-antibodies directed against pancreatic islet antigens [17][18][19]. Abnormal sensitivity to insulin in patients with type 1 diabetes was shown for the first time by Ginsberg in the 1970s [20].…”
Section: Prace Oryginalnesupporting
confidence: 88%
See 1 more Smart Citation
“…It is also noteworthy that despite lower insulin levels during the IVGTT, the relatives of diabetic patients -especially these with positive autoantibodies -had significantly higher fasting insulin concentrations and higher HOMA-IR index than had the controls. Moreover, a positive correlation between IAA levels and HOMA-IR was found in the study group, confirming the previous observations suggesting that not only decreased beta-cell secretory reserve, but also increased insulin resistance, impact upon the progression of the autoimmune process, especially in subjects with auto-antibodies directed against pancreatic islet antigens [17][18][19]. Abnormal sensitivity to insulin in patients with type 1 diabetes was shown for the first time by Ginsberg in the 1970s [20].…”
Section: Prace Oryginalnesupporting
confidence: 88%
“…To date, it is not well understood when this autoimmune destruction begins in relation to the clinical presentation of the disease and what screening tests can accurately select the subjects who are at risk for developing the disease [1]. Moreover, it has been suggested that not…”
Section: Introductionmentioning
confidence: 99%
“…Clear signs of ␤-cell damage often appear months or years before the manifestation of clinical diabetes (10), suggesting that prospective studies starting before the appearance of autoantibodies may be helpful in studying the etiology of the disease. In addition, early recognition of the individuals with ongoing ␤-cell damage may make it possibile to delay or halt ␤-cell destruction.…”
mentioning
confidence: 99%
“…Positivity of pancreatic autoantibodies in T1DM patients in Japan are 60-70% for GADA, 45-50% for IAA, and 60-65% for IA-2 antibodies at the time of diagnosis. 15 Our results indicated that GADA, IAA and ICA were positive in 80.6%, 35.5% and 6.5% of Korean patients with T1DM.Many studies have shown that siblings of patients with T1DM are at an increased risk of diabetes-related autoimmunity.11,12 Knip et al 16 reported that pancreas autoantibodies were positive in 24.1% of siblings of T1DM subjects. Onengut-Gumuscu et al 17 revealed that the pancreas autoantibodies were showed in 9% of first-degree relatives of T1DM patients in European countries.…”
mentioning
confidence: 59%